The Role of Servicescape, Word of Mouth, Perceived Value of Customer's Behavioral Intention - Arifin Djakasaputra; Juliana; Amelda Pramezwary; Rosianna Sianipar (Institute of Computer Science (IOCS), 2022)
The purpose of this research is to investigate the relationship between Servicescape, word of mouth, and the perceived value of customer behavioral intention. Non-probability sampling is used in this study. A sample of 100 respondents was used to test the relationships between specified variables using structural equation modeling (SEM). A seven-point Likert scale was used to assess all indicators. It was discovered that servicescape components have no effect on behavioral intention; however, perceived value and word of mouth have an effect on behavioral intention. To improve validity and reliability, future researchers may replicate the study with more extensive and cross-sectional segments. Future research could look into the moderating role of customer characteristics in the relationship hypothesized in this study. Increase the number of respondents, use different sampling methods, add other variables, and use different units of analysis are all suggestions for future research.